2019
DOI: 10.3889/oamjms.2019.423
|View full text |Cite
|
Sign up to set email alerts
|

The Difference in Effect of Arabica Coffee Gayo Beans and Leaf (Coffea Arabica Gayo) Extract on Decreasing Blood Sugar Levels in Healthy Mice

Abstract: BACKGROUND: High incidence rate of diabetes mellitus (DM) and increased incidence of complications from DM as well as the use of less effective antidiabetic drugs and high financing to treat demands alternative therapy. AIM: This study was conducted to determine the difference in the effect of Arabica coffee gayo bean and leaf extract on blood sugar levels in healthy mice before and after the intervention of extract and fasting and postprandial blood glucose level after consumption of glucose. METH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Epidemiological studies have shown that habitual coffee consumption may reduce the risk of Alzheimer's disease [68], and the coffee intake of male patients with primary Parkinson's disease is negatively correlated with the severity of tremor [69]. In the APP/PS2 transgenic mouse model of Alzheimer's disease in Figure 1, However, many reports have shown that many compounds in coffee can independently have neuroprotective effects, suggesting that decaffeinated coffee is also effective against neurodegenerative diseases.…”
Section: Neuroprotectionmentioning
confidence: 99%
“…Epidemiological studies have shown that habitual coffee consumption may reduce the risk of Alzheimer's disease [68], and the coffee intake of male patients with primary Parkinson's disease is negatively correlated with the severity of tremor [69]. In the APP/PS2 transgenic mouse model of Alzheimer's disease in Figure 1, However, many reports have shown that many compounds in coffee can independently have neuroprotective effects, suggesting that decaffeinated coffee is also effective against neurodegenerative diseases.…”
Section: Neuroprotectionmentioning
confidence: 99%
“…Utilization of the coffee plant is currently still focused on seeds, while coffee leaves have not been widely used either as food products or as natural mixtures for food fortification, let alone medicine. Research by Martina (2019) shows that there is no significant difference between the benefits of coffee bean extract and coffee leaf extract in healthy rats on reducing blood sugar levels. Both provide the same effect of lowering blood sugar levels compared to placebo [3].…”
Section: Introductionmentioning
confidence: 99%
“…Research by Martina (2019) shows that there is no significant difference between the benefits of coffee bean extract and coffee leaf extract in healthy rats on reducing blood sugar levels. Both provide the same effect of lowering blood sugar levels compared to placebo [3]. In Sumatra, especially coffee leaves are served as a brewed drink called "Aia Kawa" which is believed to contain polyphenol, flavonoids, and caffeine that can prevent various diseases, one of which is carcinogenic disease [4].…”
Section: Introductionmentioning
confidence: 99%